Sustainable Construction Materials in the Middle East: Model Development for Materials Selection - Madu, Taha Ahmed Omar (AUC Knowledge Fountain, 2026)
The construction industry, a major driver of economic development in the Middle East, is simultaneously a leading contributor to carbon emissions, resource depletion, and environmental degradation. Amid rapid urbanization in countries such as Egypt, Saudi Arabia, and the United Arab Emirates, the adoption of sustainable construction materials has emerged as a critical strategy for mitigating environmental and societal impacts while advancing regional development objectives. This thesis is organized along two interrelated directions: first, it delivers a comprehensive assessment of the current adoption, challenges, and opportunities associated with the use of sustainable construction materials across the three target countries; second, it develops a robust, systematic model to guide the sustainable selection of building materials. A mixed-methods approach was employed, integrating qualitative and quantitative analyses. Qualitative data were collected through expert interviews involving stakeholders from academia and industry and were analyzed using thematic analysis to uncover insights related to policy, market conditions, and supply chain dynamics. Quantitative data were gathered via pairwise comparison surveys in which experts evaluated and prioritized ten key sustainability factors spanning environmental, economic, social, and technical dimensions: climate change, pollution, construction solid waste, resource use, life-cycle cost, waste management, local economic development, human health and safety, human satisfaction, and practicability. Quantitative analysis employed the Analytic Hierarchy Process (AHP) to assign weights to these sustainability factors, followed by the application of the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to prioritize material alternatives based on their sustainability performance. Key findings reveal significant variability in market readiness, regulatory environments, and supply chain capabilities across the studied countries. Among the evaluated criteria, human health and safety, pollution, and resource use emerged as the most influential factors for material selection. The proposed decision-making model effectively ranks construction materials in line with regional priorities and demonstrates adaptability for global applications. The model highlighted differences in sustainability among the five materials, placing timber at the top, followed by recycled HDPE lumber and CEM II/A-V concrete, with clay brick and steel ranking lower in comparison. Conclusions emphasize the need for targeted policy interventions, market incentives, capacity-building initiatives, and data-driven evaluation mechanisms to accelerate the transition towards sustainable construction in the Middle East. The thesis offers a transferable framework for practitioners, policymakers, and researchers seeking to promote the broader adoption of sustainable materials in construction worldwide.